The Difficulties Resolve of Students in Learning by Using Problem Possing with Mind Mapping Technique - Fitriana Eka Chandra (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2016)
Mathematical learning should be construct to develop problem solving ability for students. One of strategy that can use in learning mathematic is Problem Possing Strategy. There are two activities students in problem possing strategy ie create the problems and looking for the solution. But, students often get dificulty when do it. Mind mapping tehnique can help student to create the problems and the solutions.Key words: problem possing, mind mapping, problem